2016
DOI: 10.1097/crd.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use and Cardiovascular Disease

Abstract: Marijuana is currently the most used illicit substance in the world. With the current trend of decriminalization and legalization of marijuana in the US, physicians in the US will encounter more patients using marijuana recreationally over a diverse range of ages and health states. Therefore, it is relevant to review marijuana's effects on human cardiovascular physiology and disease. Compared with placebo, marijuana cigarettes cause increases in heart rate, supine systolic and diastolic blood pressures, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 61 publications
1
78
0
4
Order By: Relevance
“…Following SCs intake, sinus tachycardia is the most frequent incident reported, with an overall 40% prevalence. Hypertension is often concomitant, up to one‐fourth of cases . Based on experimental data and compared to the effects of smoking marijuana, hypertension was not the more frequent change in blood pressure that is expected and the exact mechanism of occurrence remains to be clarified.…”
Section: Effects In Humansmentioning
confidence: 99%
“…Following SCs intake, sinus tachycardia is the most frequent incident reported, with an overall 40% prevalence. Hypertension is often concomitant, up to one‐fourth of cases . Based on experimental data and compared to the effects of smoking marijuana, hypertension was not the more frequent change in blood pressure that is expected and the exact mechanism of occurrence remains to be clarified.…”
Section: Effects In Humansmentioning
confidence: 99%
“…3,5 A recent review suggested that smoking marijuana increases the risk of MI onset by a factor of 4.8 for the 60 minutes after marijuana consumption, and increases the annual risk of MI in the daily marijuana user from 1.5% to 3% per year. 6 Does all this mean marijuana should not be legalized? Absolutely not.…”
mentioning
confidence: 99%
“…Despite marijuana users being of male gender mainly and with less stress than nonusers, when faced with stress, cardiomyopathy users were more likely to go into cardiac arrest (2.4% vs. 0.8%) and to require an implanted defibrillator (2.4% vs. 0.6%). This study did have its limitations because researchers were unable to determine how frequently marijuana users were using marijuana, or what the timeframe was between the use of marijuana and occurrence of stress cardiomyopathy (Franz & Frishman, ).…”
Section: Introductionmentioning
confidence: 99%